Emergency Department Documentation of Alleged Police Use of Excessive Force in Cases Where Formal Complaints Are Ultimately Filed. (December 2018) - Strote, Jared; Hickman, Matthew J.
Abstract : Background: Emergency physicians encounter patient concerns of police use of excessive force (UOEF). However, unlike other forms of potential assault, there are no guidelines for documentation of these encounters. Our objective was to examine the adequacy of emergency department documentation of injuries from police encounters where formal complaints of UOEF were later filed with the law enforcement agency. Methods: A retrospective cohort design was used, identifying all citizen complaints of UOEF to a single police department in a 3-year period. Emergency department records associated with these encounters were then accessed and evaluated using standards for other forms of abuse and assault. Results: Of 235 complaints, 33 (14.0%) presented to the emergency department within 7 days of the incident and were able to provide a history. For these subjects, 13 charts (39.4%) contained 3 or more of the 4 components thought to be necessary in cases of potential assault, and 11 (33.3%) contained documentation that should not be present: the guilt of the patient, subjective terminology by the provider, and/or documentation of law enforcement's description of the events as the only factual history. Of the total, 14 charts (42.4%) documented the patient's concern for UOEF. Conclusions: In this limited study, documentation of encounters where patients later filed a formal complaint of UOEF by law enforcement did not meet the standards for other forms of assault and abuse, having the potential to impact both the citizens and officers involved. Further study is necessary to identify the best practice guidelines for emergency physicians when they encounter patients injured in police encounters.